Some of the Twenty-First Century Skills Practice by Female Teachers and their Relationship with Self-Esteem among Female Students with Learning Disabilities in Primary Schools - Reem Jaber Doushi; Kowthar J. Ali (Eximia, 2022)
This research aims to divulge the relationships between female teachers’ practice of some twenty-first century skills and self-esteem amongst female students with learning disabilities at the primary school in Jubail in light of some variables (academic qualification, years of experience, type of disability). The descriptive correlative approach has been used for the nature of the current research. The intentionally chosen sample members were (20) female teachers of learning disabilities in Jubail city. The results indicated that there was no statistically significant relationship between female teachers’ practice of twenty-first century skills and self-esteem among female students with learning disabilities in primary schools. Besides, an increase in the level of female teachers’ practice of twenty-first century skills. In addition, there were no statistically significant differences between the practice of twenty-first century skills and the academic qualification, years of experience, and type of disability variable. Of the research recommendation, intensifying the efforts of teachers in practicing the skills of the twenty-first century to include the personal aspects, not just the academic aspects, so that they are within their plans, and are based on the principle of supportive services, which supports their self-esteem.